A flame-retardant ethylene-propylene-diene rubber composition and a method for preparing the same
Patent Information
- Application Number
- CN202611228993.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]现有阻燃型三元乙丙发泡橡胶通常通过提高阻燃剂添加量来提升阻燃等级,但无卤阻燃剂加入量较高时,会明显提高胶料黏度和成品硬度,使胶料在混炼、塑化和发泡硫化过程中容易出现阻燃剂分散不均、泡孔壁强度不足、局部塌孔、密度波动和尺寸收缩等问题,导致材料虽然阻燃性能提高,但低硬度、发泡倍率和密封回弹性能下降,难以稳定制备硬度较低且阻燃等级较高的泡棉产品
[0034]该阻燃型三元乙丙发泡橡胶组合物及其制备方法,通过三元乙丙橡胶、乙烯-丙烯共聚物和石蜡油形成柔性橡塑基体,并配合氢氧化铝、氢氧化镁、膨胀型阻燃剂和硼酸锌构成低卤阻燃体系,使组合物在保持较高无卤阻燃剂含量的同时,仍具有较好的塑化融合性和发泡成型稳定性;同时,通过先进行基体塑化预混和阻燃填料分散,再低温加入发泡硫化体系,并在后续高温塑化、发泡和硫化过程中实现泡孔扩张与交联定型的匹配,使制得的三元乙丙发泡橡胶具有低硬度、高发泡倍率、低收缩率、密度稳定和离火自熄性能,可用于新能源汽车密封、防水、阻燃部件以及光伏发电储能柜隔热阻燃防护部件,并能够根据不同使用要求调整硬度、密度、尺寸和阻燃等级,从而降低生产难度和综合成本。
Smart Images

Figure CN123004044A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of EPDM rubber technology, specifically to a flame-retardant EPDM foamed rubber composition and its preparation method. Background Technology
[0002] EPDM rubber possesses good weather resistance, ozone resistance, water resistance, and elastic recovery properties, and is commonly used in automotive seals, building sealing materials, protective gaskets for energy storage equipment, and other outdoor protective components. However, with the increasing demands for waterproofing, heat insulation, cushioning, and flame retardancy in battery compartments, door sealing areas, chassis protection areas, and photovoltaic energy storage cabinets of new energy vehicles, ordinary EPDM foamed rubber can no longer simultaneously meet the requirements of low hardness, high foaming ratio, low shrinkage, and high flame retardancy. Especially in the application scenarios of new energy vehicles and energy storage cabinets, sealing materials not only need to have good compression resilience and dimensional stability, but also need to be able to quickly self-extinguish upon exposure to heat or fire, and minimize the use of halogenated flame retardants to reduce the risk of corrosive gases and smoke during combustion.
[0003] Existing flame-retardant EPDM foam rubber typically improves its flame retardancy rating by increasing the amount of flame retardant added. However, a high amount of halogen-free flame retardant significantly increases the viscosity and hardness of the rubber compound. This can lead to problems such as uneven dispersion of the flame retardant, insufficient cell wall strength, localized cell collapse, density fluctuations, and dimensional shrinkage during mixing, plasticizing, and foaming vulcanization. As a result, while the flame retardant performance is improved, the material exhibits lower hardness, reduced foaming ratio, and decreased sealing resilience, making it difficult to stably produce foam products with lower hardness and higher flame retardancy ratings. On the other hand, some existing processes lack sufficient control over the matching of matrix plasticizing, flame retardant filler dispersion, timing of foaming agent addition, and vulcanization and setting stages. This can easily cause premature decomposition of the foaming agent, localized concentration of the vulcanizing agent, or asynchronous cell expansion and cross-linking and setting. Consequently, the batch stability of the products is poor, production efficiency is low, and overall costs are high, making it difficult to meet the continuous production requirements of flame-retardant foam rubber products with different hardness, thickness, and size. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a flame-retardant EPDM foamed rubber composition and its preparation method, thereby solving the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] This invention provides a flame-retardant EPDM foamed rubber composition, comprising the following components by weight:
[0007] 100 parts EPDM rubber, 10-35 parts ethylene-propylene copolymer, 20-60 parts paraffin oil, 80-180 parts aluminum hydroxide, 40-120 parts magnesium hydroxide, 20-60 parts intumescent flame retardant, 5-20 parts zinc borate, 5-25 parts carbon black, 5-20 parts silica, 3-8 parts zinc oxide, 1-3 parts stearic acid, 4-12 parts foaming agent, 2-8 parts foaming aid, 2-6 parts vulcanizing agent, 1-5 parts crosslinking aid, and 1-4 parts antioxidant.
[0008] The EPDM / POE composite rubber matrix is formed by combining the EPDM and ethylene-propylene copolymer in the specified mass parts. The ethylene-propylene copolymer is dispersed in the continuous phase of the EPDM rubber to form a biphase blend structure with a rubber elastic phase and a flexible polyolefin phase.
[0009] The EPDM / POE composite rubber matrix and paraffin oil together constitute the foamed rubber matrix. The aluminum hydroxide, magnesium hydroxide, intumescent flame retardant and zinc borate together form a halogen-free flame retardant system. The foaming agent, foaming aid, vulcanizing agent and crosslinking aid together form a foaming vulcanization system.
[0010] The EPDM / POE composite rubber matrix is used to maintain the processing fluidity and cell support capacity of the rubber compound under the condition of adding high content of halogen-free flame retardant filler, so that the composition forms a stable cell structure after foaming and vulcanization.
[0011] This flame-retardant EPDM foamed rubber composition is used as a foamed rubber material for sealing, waterproofing, and flame-retardant components of new energy vehicles or for heat-insulating and flame-retardant protective components of photovoltaic power generation energy storage cabinets.
[0012] To further optimize this technical solution, the EPDM rubber is an EPDM rubber with an ethylene content of 45%-70% and a Mooney viscosity of 40-80, and the third monomer in the EPDM rubber is ethylene-ide norbornene.
[0013] To further optimize this technical solution, the melt flow rate of the ethylene-propylene copolymer is 0.5-5 g / 10 min, and the Shore A hardness is not higher than 75 degrees.
[0014] The ethylene-propylene copolymer and EPDM rubber are melt-blended to form an EPDM / POE composite rubber matrix, wherein the ethylene-propylene copolymer is distributed in the interstitial region of the EPDM rubber molecular chains to improve the flexibility and filler capacity of the composite rubber matrix.
[0015] To further optimize this technical solution, aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler, wherein the average particle size of aluminum hydroxide is 1-8 μm and the average particle size of magnesium hydroxide is 0.8-6 μm.
[0016] To further optimize this technical solution, the intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components, and a charring agent, with a mass ratio of 20-45:5-20:5-20, and the degree of polymerization of the ammonium polyphosphate is not less than 500.
[0017] By limiting the composition of the acid source, gas source and carbon source of the intumescent flame retardant, an intumescent carbon layer is formed on the surface of the foam when the material is exposed to fire. This intumescent carbon layer covers the surface of the EPDM foamed rubber and prevents heat and oxygen from continuing to enter the internal cell structure.
[0018] To further optimize this technical solution, the average particle size of the zinc borate is 1-5 μm, and the moisture content is not higher than 1.5%.
[0019] The zinc borate is dispersed between the metal hydroxide and the intumescent flame retardant to form a boron-containing glass-like protective layer on the burning surface and to improve the density and crack resistance of the intumescent char layer.
[0020] To further optimize this technical solution, the carbon black and silica together constitute a reinforcing filler, wherein the iodine absorption value of the carbon black is 20-80 mg / g, and the specific surface area of the silica is 120-220 m² / g.
[0021] To further optimize this technical solution, the foaming agent is azodicarbonamide or modified azodicarbonamide, with a decomposition temperature of 150-210℃;
[0022] The foaming agent is zinc oxide, urea-based foaming agents, or a combination thereof.
[0023] To further optimize this technical solution, the vulcanizing agent is a peroxide vulcanizing agent, and the crosslinking aid is triallyl isocyanurate or trimethylolpropane trimethacrylate;
[0024] By forming a heat-resistant crosslinking network through peroxide vulcanizing agent and crosslinking aid, EPDM rubber, ethylene-propylene copolymer and flame-retardant filler are fixed into a stable cell skeleton after high-temperature plasticization.
[0025] A method for preparing a flame-retardant EPDM foamed rubber composition, based on the above-mentioned flame-retardant EPDM foamed rubber composition, includes the following steps:
[0026] S1. Matrix plasticizing premix: EPDM rubber, ethylene-propylene copolymer and paraffin oil are mixed to form a flexible rubber-plastic matrix;
[0027] S2, Halogen-free flame retardant filler dispersion: Add aluminum hydroxide, magnesium hydroxide, intumescent flame retardant and zinc borate to form a composite flame retardant system;
[0028] S3, Reinforcing and Stabilizing System Mixing: Add carbon black, silica, zinc oxide, stearic acid and antioxidants to improve the stability of the cell skeleton;
[0029] S4. Low-temperature addition to the foaming and vulcanization system: Add the foaming agent, foaming aid, vulcanizing agent, and crosslinking aid at a temperature below the decomposition temperature of the foaming agent;
[0030] S5. Film forming and curing: The rubber material is calendered or extruded into a blank and then cured to ensure a balanced distribution of components.
[0031] S6. High-temperature plasticizing and foaming vulcanization: The preform is subjected to high-temperature plasticizing, foaming and vulcanization to expand the cell structure and cross-link and solidify it.
[0032] S7. Cooling, shaping and post-treatment: Cooling, cutting or post-curing the foamed vulcanized products to obtain flame-retardant foamed rubber products.
[0033] Compared with the prior art, the present invention provides a flame-retardant EPDM foamed rubber composition and its preparation method, which has the following beneficial effects:
[0034] This flame-retardant EPDM foamed rubber composition and its preparation method involve forming a flexible rubber-plastic matrix using EPDM rubber, ethylene-propylene copolymer, and paraffin oil, and then combining it with aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate to form a low-halogen flame-retardant system. This allows the composition to maintain a high content of halogen-free flame retardant while still exhibiting good plasticizing compatibility and foaming stability. Furthermore, by first plasticizing and premixing the matrix and dispersing the flame-retardant filler, and then adding the foaming and vulcanizing system at a low temperature, and then achieving a match between cell expansion and cross-linking during subsequent high-temperature plasticizing, foaming, and vulcanizing processes, the resulting EPDM foamed rubber exhibits low hardness, high foaming ratio, low shrinkage, stable density, and self-extinguishing properties. It can be used for sealing, waterproofing, and flame-retardant components in new energy vehicles, as well as heat-insulating and flame-retardant protective components for photovoltaic power generation energy storage cabinets. The hardness, density, size, and flame-retardant rating can be adjusted according to different application requirements, thereby reducing production difficulty and overall cost. Attached Figure Description
[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1 This is a schematic flowchart of a method for preparing a flame-retardant EPDM foamed rubber composition proposed in this invention. Detailed Implementation
[0037] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0038] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places throughout this specification does not necessarily refer to the same embodiment, nor is it a single embodiment or an embodiment selectively excluded from other embodiments.
[0040] A flame-retardant EPDM foamed rubber composition, comprising the following components by weight:
[0041] 100 parts EPDM rubber, 10-35 parts ethylene-propylene copolymer, 20-60 parts paraffin oil, 80-180 parts aluminum hydroxide, 40-120 parts magnesium hydroxide, 20-60 parts intumescent flame retardant, 5-20 parts zinc borate, 5-25 parts carbon black, 5-20 parts silica, 3-8 parts zinc oxide, 1-3 parts stearic acid, 4-12 parts foaming agent, 2-8 parts foaming aid, 2-6 parts vulcanizing agent, 1-5 parts crosslinking aid, and 1-4 parts antioxidant.
[0042] Among them, ethylene propylene diene monomer (EPDM) rubber serves as the main rubber, providing weather resistance, water resistance, sealing performance, and elastic recovery; ethylene-propylene copolymer is used to improve the softness and processing fluidity after the addition of a large amount of halogen-free flame retardant, allowing the foamed rubber to maintain a stable cell structure at lower hardness; paraffin oil is used to adjust the material's hardness and plasticization degree, enabling the composition to be adjusted in terms of softness according to different application requirements such as sealing strips for new energy vehicles and thermal insulation gaskets for photovoltaic energy storage cabinets; aluminum hydroxide and magnesium hydroxide, as the main halogen-free flame retardants, release water of crystallization and absorb heat when heated, reducing the combustion temperature and minimizing the introduction of halogens; intumescent flame retardants are used to form expanded char on the burning surface. The composition comprises a layer to enhance self-extinguishing capability upon removal from flame, ensuring the material's flame retardant performance meets UL94-V0 requirements. Zinc borate synergistically improves flame retardancy and smoke suppression, and enhances the stability of the char layer under high-filling conditions of the flame retardant. Carbon black and silica strengthen the foam skeleton, reduce shrinkage after foaming, and stabilize density. Zinc oxide and stearic acid promote the vulcanization system reaction. Foaming agents and foaming aids form a uniform closed-cell or semi-closed-cell structure, increasing the foaming ratio. Vulcanizing agents and crosslinking aids form a stable crosslinking network, ensuring full fusion of components after high-temperature plasticization, reducing hardness and density dispersion. Antioxidants improve long-term heat aging resistance, weather resistance, and service stability. This composition, through the matching of a high proportion of halogen-free flame retardant with the foaming vulcanization system, enables the material to possess flame retardant, sealing, waterproof, heat insulation, and low shrinkage properties under low halogen content conditions. Hardness, density, foaming ratio, and flame retardant rating can be adjusted by modifying the amounts of paraffin oil, foaming agent, flame retardant, and crosslinking aids.
[0043] The EPDM / POE composite rubber matrix is formed by combining the EPDM and ethylene-propylene copolymer in the specified mass parts. The ethylene-propylene copolymer is dispersed in the continuous phase of the EPDM rubber to form a biphase blend structure with a rubber elastic phase and a flexible polyolefin phase.
[0044] The EPDM / POE composite rubber matrix and paraffin oil together constitute the foamed rubber matrix. The aluminum hydroxide, magnesium hydroxide, intumescent flame retardant and zinc borate together form a halogen-free flame retardant system. The foaming agent, foaming aid, vulcanizing agent and crosslinking aid together form a foaming vulcanization system.
[0045] The EPDM / POE composite rubber matrix is used to maintain the processing fluidity and cell support capacity of the rubber compound under the condition of adding high content of halogen-free flame retardant filler, so that the composition forms a stable cell structure after foaming and vulcanization.
[0046] This flame-retardant EPDM foamed rubber composition is used as a foamed rubber material for sealing, waterproofing, and flame-retardant components of new energy vehicles or for heat-insulating and flame-retardant protective components of photovoltaic power generation energy storage cabinets.
[0047] Ethylene propylene diene monomer (EPDM) rubber is an EPDM rubber with an ethylene content of 45%-70% and a Mooney viscosity of 40-80, and the third monomer in the EPDM rubber is ethylene-ide norbornene. By limiting the ethylene content and Mooney viscosity, the rubber matrix still has sufficient mixing containment and melt support after adding a high proportion of halogen-free flame retardant, avoiding cell collapse due to insufficient rubber strength. At the same time, the material maintains low shrinkage and stable density after foaming and vulcanization, making it suitable for continuous molding of sealing parts for new energy vehicles and heat-insulating and flame-retardant gaskets for energy storage cabinets.
[0048] The melt flow rate of the ethylene-propylene copolymer is 0.5-5 g / 10 min, and the Shore A hardness is not higher than 75 degrees. The ethylene-propylene copolymer and EPDM rubber are melt-blended to form an EPDM / POE composite rubber matrix, in which the ethylene-propylene copolymer is distributed in the interstitial region of the EPDM rubber molecular chain to improve the flexibility and filler capacity of the composite rubber matrix. This allows the foamed rubber to maintain continuous cell walls and good resilience when the hardness is 10-25 degrees, thus meeting the requirements for low-hardness sealing, waterproofing and thermal insulation cushioning.
[0049] Paraffin oil is a naphthenic paraffin oil or paraffin-based rubber oil with a kinematic viscosity of 60-180 mm² / s at 40°C and a flash point of not less than 180°C. By limiting the viscosity and flash point of the paraffin oil, it is prevented from volatilizing in large quantities during high-temperature plasticizing and foaming vulcanization, and it can uniformly enter the flexible rubber-plastic phase formed by EPDM rubber and ethylene-propylene copolymer. It is used to adjust the degree of plasticization of the rubber compound, the hardness of the finished product, and the cell expansion capacity, and to avoid foam shrinkage, surface stickiness, or density fluctuations caused by the migration of low-viscosity oil.
[0050] Aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler. The average particle size of aluminum hydroxide is 1-8 μm, and the average particle size of magnesium hydroxide is 0.8-6 μm. By making the two metal hydroxides have similar particle sizes and limiting the ratio, the flame-retardant filler forms a continuous endothermic flame-retardant phase in the rubber matrix. When heated during combustion, it releases bound water in stages and reduces the surface temperature of the material. At the same time, it reduces the problem of sudden increase in processing viscosity and cell rupture caused by high filling of a single flame retardant, thus taking into account low halogen flame retardancy, cell stability and foaming ratio.
[0051] The intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components, and a charring agent, with a mass ratio of 20-45:5-20:5-20. The degree of polymerization of the ammonium polyphosphate is not less than 500. By limiting the acid source, gas source, and char source composition of the intumescent flame retardant, an expanded char layer is formed on the surface of the foam after the material is exposed to fire. This expanded char layer covers the surface of the EPDM foam rubber and blocks heat and oxygen from continuing to enter the internal cell structure, thereby improving the self-extinguishing performance after the flame is removed. It also forms a synergistic flame retardant system with aluminum hydroxide and magnesium hydroxide, reducing the total amount of flame retardant required to achieve the UL94-V0 flame retardant rating.
[0052] The average particle size of zinc borate is 1-5 μm, and the moisture content is not higher than 1.5%. Zinc borate is dispersed between metal hydroxide and intumescent flame retardant to form a borosilicate glass-like protective layer on the burning surface and improve the density and crack resistance of the intumescent char layer. By limiting the particle size and moisture content of zinc borate, local macropores, pores and surface pinholes caused by agglomeration or moisture release during mixing and foaming vulcanization are avoided, so that the flame-retardant foam has both a stable cell structure and smoke suppression and flame retardant properties.
[0053] Carbon black and silica together constitute reinforcing fillers. Carbon black has an iodine absorption value of 20-80 mg / g, while silica has a specific surface area of 120-220 m² / g. Carbon black provides basic reinforcement and dimensional stability, while silica improves the cell wall strength and the bonding ability of flame-retardant fillers. This makes the foamed and vulcanized foam less prone to significant dimensional shrinkage during compression, rebound, and thermal aging. At the same time, it reduces filler sedimentation and local density deviation caused by the addition of a large amount of halogen-free flame retardant.
[0054] The foaming agent is azodicarbonamide or modified azodicarbonamide, with a decomposition temperature of 150-210℃; the foaming aid is zinc oxide, urea-based foaming aid, or a combination thereof; by matching the decomposition temperature of the foaming agent with the crosslinking initiation temperature of the vulcanization system, the rubber compound releases gas and expands the cells after the crosslinking network begins to form, avoiding premature gas release leading to air loss or premature gas release leading to insufficient cells, thereby increasing the foaming ratio and maintaining stable density.
[0055] The vulcanizing agent is a peroxide vulcanizing agent, and the crosslinking aid is triallyl isocyanurate or trimethylolpropane trimethacrylate. The peroxide vulcanizing agent and the crosslinking aid form a heat-resistant crosslinking network, which fixes the EPDM rubber, ethylene-propylene copolymer and high-part flame-retardant filler into a stable cell skeleton after high-temperature plasticization, preventing the cells from continuing to shrink or collapse after foaming, and improving the long-term dimensional stability of the material in the high-temperature environment of the battery compartment, door sealing area and energy storage cabinet of new energy vehicles.
[0056] In this invention, the combination of 100 parts of EPDM rubber and 10-35 parts of ethylene-propylene copolymer is not a simple elastomer replacement or conventional toughening, but rather a specific combination with a high-filler halogen-free flame-retardant system and a foaming vulcanization system to achieve the target performance. Specifically, when the ethylene-propylene copolymer is less than 10 parts, the flexible polyolefin phase formed in the continuous phase of EPDM rubber is insufficient, making it difficult to effectively alleviate the problems of rubber hardening, filler agglomeration, and cell wall embrittlement caused by the high proportion of aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate. The hardness of the resulting foam is easily higher than 25 degrees, and the low hardness sealing and cushioning performance is insufficient. When the ethylene-propylene copolymer is more than 35 parts, the proportion of flexible polyolefin phase in the composite rubber matrix is too high, which easily weakens the heat resistance and dimensional retention of the EPDM crosslinked skeleton, leading to cell shrinkage, increased compression set, or decreased load-bearing stability of the flame-retardant filler after foaming and vulcanization. Therefore, the ethylene-propylene copolymer is limited to 10-35 parts to form an EPDM / POE composite rubber matrix with 100 parts of EPDM rubber. In this matrix, EPDM rubber provides a continuous crosslinking skeleton and a weather-resistant and heat-resistant base, while the ethylene-propylene copolymer provides a flexible phase and filler accommodation space. Together, they enable the material to maintain processable compound flowability and foaming support even with the addition of 80-180 parts of aluminum hydroxide, 40-120 parts of magnesium hydroxide, 20-60 parts of intumescent flame retardant, and 5-20 parts of zinc borate. Furthermore, the total amount of the halogen-free flame retardant system is 145-380 parts, wherein aluminum hydroxide and magnesium hydroxide reduce the heat release of combustion by absorbing heat and dehydrating, the intumescent flame retardant forms a heat-insulating covering layer by expanding through char formation, and zinc borate improves the integrity of the char layer by stabilizing char and suppressing smoke. If the total amount of flame retardant is too low, it will be difficult for the material to meet the requirements of oxygen index ≥28% and UL94 V-0 self-extinguishing rating. If the total amount of flame retardant is too high, it will significantly increase the viscosity of the system and destroy the uniformity of cell expansion, resulting in increased foam hardness, increased density fluctuations, and decreased foaming ratio. This application defines the proportions of EPDM / POE, paraffin oil (20-60 parts), foaming agent (4-12 parts), vulcanizing agent (2-6 parts), and crosslinking agent (1-5 parts) to achieve a balanced relationship between the flexible rubber-plastic matrix, flame-retardant filler network, and foaming crosslinking network within the same formulation system. POE and paraffin oil together reduce the hardness increase trend of the high-filler system, the foaming agent provides cell expansion capability, the peroxide vulcanizing agent and crosslinking agent fix the cell skeleton, and the reinforcing filler improves the dimensional stability of the cell walls. Therefore, the composition does not achieve flame retardancy solely by adding flame retardant, but rather, based on the EPDM / POE composite rubber matrix carrying a high content of halogen-free flame retardant, the product simultaneously meets the comprehensive performance requirements of Shore A hardness 10-25, UL94 V-0 flame retardancy, oxygen index ≥28%, low shrinkage, and stable density.
[0057] A method for preparing a flame-retardant EPDM foamed rubber composition includes the following steps:
[0058] S1. Matrix Plasticizing Premix: Weigh out EPDM rubber, ethylene-propylene copolymer, and paraffin oil according to the formula mass parts. First, put the EPDM rubber into a mixer for initial plasticizing. After the rubber compound forms a continuous roll wrapping or continuous shearing state, add the ethylene-propylene copolymer and continue mixing to disperse the ethylene-propylene copolymer in the EPDM rubber to form a flexible rubber-plastic matrix. Then, add the paraffin oil in batches to allow the paraffin oil to gradually penetrate into the flexible rubber-plastic matrix. Control the mixing temperature at 70-105℃ and the mixing time at 4-10 minutes. When discharging, there should be no obvious free oil or unplasticized rubber lumps on the surface of the rubber compound.
[0059] This step is used to form a base adhesive phase that can support a high proportion of halogen-free flame retardant, avoiding problems such as flame retardant agglomeration, uneven foaming hardness, or localized high density caused by insufficient plasticization of the adhesive when flame retardant fillers are added in a single step later.
[0060] S2. Halogen-free flame-retardant filler dispersion: Based on the flexible rubber-plastic matrix obtained in the previous step, aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate are sequentially added to a Banbury mixer for filler dispersion and mixing. Aluminum hydroxide and magnesium hydroxide are added first, forming a basic endothermic flame-retardant filler phase in the colloidal phase. Then, the intumescent flame retardant is added, dispersing it between the metal hydroxides. Finally, zinc borate is added, distributing it at the interface between the metal hydroxides and the intumescent flame retardant. The mixing temperature is controlled at 90-130℃, the mixing time is 5-15 minutes, and the discharge temperature should not exceed 135℃.
[0061] Through this sequence, the high-filled halogen-free flame retardant is gradually coated by the rubber matrix, forming a composite flame retardant structure with metal hydroxide heat absorption and flame retardancy, intumescent flame retardant charring and heat insulation, and zinc borate char stabilization and smoke suppression, thereby improving the self-extinguishing ability while maintaining a low halogen content.
[0062] S3. Reinforcing and Stabilizing System Mixing: Based on the flame-retardant rubber compound obtained in the previous step, add carbon black, silica, zinc oxide, stearic acid, and antioxidants for further mixing. This ensures that the carbon black and silica are dispersed within the cell skeleton formation area of the flame-retardant rubber compound, while zinc oxide and stearic acid are dispersed in the rubber phase to form a vulcanization-promoting auxiliary system. The antioxidants are dispersed in the continuous phase of the rubber compound. The mixing temperature in this stage is controlled at 95-125℃, and the mixing time is 3-8 minutes. After mixing, the rubber compound is thin-passed or re-mixed to control the compound thickness at 3-8 mm, and then cooled to room temperature.
[0063] This step enables the reinforcing filler and flame retardant filler to form a stable filler network, improving the strength and dimensional stability of the foam cells after foaming, reducing the shrinkage rate of the foam during high-temperature vulcanization, subsequent cooling, and long-term use, while avoiding hardness dispersion and localized cell collapse caused by the addition of a large amount of halogen-free flame retardant.
[0064] S4. Low-temperature addition to the foaming and vulcanization system: Based on the rubber compound cooled in the previous step, transfer the rubber compound to a two-roll mill or a low-temperature internal mixer, and control the temperature of the rubber compound to be lower than the initial decomposition temperature of the foaming agent, preferably controlled at 45-80℃. Add the foaming agent, foaming aid, vulcanizing agent and crosslinking aid in sequence, and mix them evenly for 3-8 minutes. During the mixing process, control the roller gap or rotor shear strength to ensure that the foaming agent and vulcanizing agent are evenly distributed without premature decomposition or premature crosslinking.
[0065] The key to this step is to add the foaming system and the vulcanization system at a lower temperature so that the gas release stage of the foaming agent matches the cross-linking and shaping stage of the vulcanizing agent. This avoids gas leakage, excessively large openings, or insufficient foaming ratio caused by premature decomposition of the foaming agent, and also avoids local concentration of the vulcanizing agent causing foam hard spots, scorching, or density fluctuations.
[0066] S5. Film Forming and Curing: Based on the rubber compound containing the foaming vulcanization system obtained in the previous step, calender or extrude it into rubber sheets, strips, or preforms with a thickness of 1-20mm, controlling the forming temperature below 90℃. After forming, the preforms are left to stand at 15-35℃ for 2-24 hours to allow the paraffin oil, flame retardant filler, reinforcing filler, foaming agent, and vulcanizing agent to achieve a relatively balanced distribution within the rubber compound. During the curing process, the surface of the preform should remain flat, without obvious oil separation, powdering, or pre-foaming.
[0067] This step is used to reduce the internal stress and component concentration gradient after mixing, so that the cells can be generated, expanded and shaped synchronously during subsequent foaming and vulcanization, thereby ensuring the density stability and shrinkage stability of products with different thicknesses, hardnesses and sizes.
[0068] S6. High-temperature plasticizing and foaming vulcanization: Based on the preform obtained in the previous step, it is placed into a mold, continuous foaming oven or flat vulcanizing equipment for high-temperature plasticizing and foaming vulcanization treatment. The treatment temperature is 155-190℃ and the treatment time is 5-25min. In the initial stage of heating, the rubber phase, paraffin oil and high part of halogen-free flame retardant are further integrated. In the middle stage, the foaming agent decomposes and releases gas and promotes the formation of cells in the rubber compound. In the later stage, the vulcanizing agent and crosslinking agent form a crosslinking network and fix the cell structure.
[0069] This step allows the high flame-retardant filler system and the foaming system to complete plasticization, gas expansion, and cross-linking during the same heat treatment process. It can maintain a high foaming ratio under high flame retardant content conditions and enable the product to obtain low hardness, low shrinkage, stable density, and self-extinguishing properties after flame removal.
[0070] S7. Cooling, Shaping, and Post-treatment: Based on the product that has undergone foaming and vulcanization in the previous step, the product is removed from the mold or continuous foaming equipment and allowed to cool naturally or in stages. After cooling to room temperature, it is cut, punched, trimmed, or laminated with adhesive. For foams with greater thickness or higher flame retardant content, a post-curing treatment can be performed at 60-90℃ for 1-4 hours to further release internal stress and stabilize dimensions. The flame-retardant EPDM foamed rubber composition after post-treatment forms a closed-cell or semi-closed-cell foam structure, which can be used for sealing, waterproofing, and flame-retardant components in new energy vehicles, as well as heat-insulating and flame-retardant protective components for photovoltaic power generation energy storage cabinets. By adjusting the amount of paraffin oil, flame retardant, foaming agent, and crosslinking aid, products with different hardness, density, foaming ratio, and flame retardant rating can be obtained.
[0071] Example 1:
[0072] A flame-retardant EPDM foamed rubber composition comprises, by weight parts: 100 parts EPDM rubber, 10 parts ethylene-propylene copolymer, 20 parts paraffin oil, 80 parts aluminum hydroxide, 40 parts magnesium hydroxide, 20 parts intumescent flame retardant, 5 parts zinc borate, 5 parts carbon black, 5 parts silica, 3 parts zinc oxide, 1 part stearic acid, 4 parts foaming agent, 2 parts foaming aid, 2 parts vulcanizing agent, 1 part crosslinking aid, and 1 part antioxidant.
[0073] Ethylene propylene diene monomer (EPDM) rubber, ethylene-propylene copolymer, and paraffin oil together form the foamed rubber matrix. Aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate together form the halogen-free flame retardant system. Foaming agent, foaming aid, vulcanizing agent, and crosslinking aid together form the foamed vulcanization system.
[0074] Ethylene propylene diene monomer (EPDM) rubber is an EPDM rubber with an ethylene content of 57.5% and a Mooney viscosity of 60, and the third monomer in the EPDM rubber is ethylene-ide norbornene.
[0075] The melt flow rate of the ethylene-propylene copolymer is 2.75 g / 10 min, and the Shore A hardness is 75 degrees.
[0076] The paraffin oil is a naphthenic paraffin oil with a kinematic viscosity of 120 mm² / s at 40°C and a flash point of 180°C.
[0077] Aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler, with aluminum hydroxide having an average particle size of 4.5 μm and magnesium hydroxide having an average particle size of 3.4 μm.
[0078] The intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components, and a charring agent, with a mass ratio of 32.5:12.5:12.5. The degree of polymerization of the ammonium polyphosphate is 500.
[0079] The average particle size of zinc borate is 3 μm, and the moisture content is 1.5%.
[0080] Carbon black and silica together constitute the reinforcing filler, with carbon black having an iodine absorption value of 50 mg / g and silica having a specific surface area of 170 m² / g.
[0081] The foaming agent is azodicarbonamide, with a decomposition temperature of 180℃; the foaming aid is a urea-based foaming aid.
[0082] The vulcanizing agent is dicumyl peroxide, and the crosslinking aid is triallyl isocyanurate.
[0083] A method for preparing a flame-retardant EPDM foamed rubber composition includes the following steps:
[0084] S1. Matrix Plasticizing Premix: Weigh out EPDM rubber, ethylene-propylene copolymer, and paraffin oil according to the formula mass parts. First, put the EPDM rubber into a mixer for initial plasticizing. After the rubber compound forms a continuous roll wrapping or continuous shearing state, add the ethylene-propylene copolymer and continue mixing to disperse the ethylene-propylene copolymer in the EPDM rubber to form a flexible rubber-plastic matrix. Then, add the paraffin oil in batches to allow the paraffin oil to gradually penetrate into the flexible rubber-plastic matrix. Control the mixing temperature at 87.5℃ and the mixing time at 7 minutes. When discharging, there should be no obvious free oil or unplasticized rubber lumps on the surface of the rubber compound.
[0085] S2. Halogen-free flame-retardant filler dispersion: Based on the flexible rubber-plastic matrix obtained in the previous step, aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate are sequentially added to a Banbury mixer for filler dispersion and mixing. Aluminum hydroxide and magnesium hydroxide are added first, allowing the two metal hydroxides to form a basic endothermic flame-retardant filler phase in the colloidal phase. Then, the intumescent flame retardant is added, dispersing it between the metal hydroxides. Finally, zinc borate is added, distributing it at the interface between the metal hydroxides and the intumescent flame retardant. The mixing temperature is controlled at 110℃, the mixing time at 10 minutes, and the discharge temperature at 135℃.
[0086] S3. Reinforcing and Stabilizing System Mixing: Based on the flame-retardant rubber compound obtained in the previous step, carbon black, silica, zinc oxide, stearic acid, and antioxidants are added and mixed further. This ensures that the carbon black and silica are dispersed within the cell skeleton formation area of the flame-retardant rubber compound, that zinc oxide and stearic acid are dispersed in the rubber phase to form a vulcanization-promoting auxiliary system, and that the antioxidants are dispersed in the continuous phase of the rubber compound. The mixing temperature in this stage is controlled at 110℃, and the mixing time is 5.5 minutes. After mixing, the rubber compound is thin-passed or re-mixed to control the compound thickness at 5.5 mm, and then cooled to room temperature.
[0087] S4. Low-temperature addition of foaming vulcanization system: Based on the rubber compound cooled in the previous step, transfer the rubber compound into the open mill, control the rubber compound temperature at 62.5℃, add the foaming agent, foaming aid, vulcanizing agent and crosslinking aid in sequence, and mix evenly for 5.5 minutes; during the mixing process, control the roller gap and rotor shear strength to ensure that the foaming agent and vulcanizing agent are evenly distributed without premature decomposition or premature crosslinking.
[0088] S5. Film Forming and Curing: Based on the rubber compound containing the foaming vulcanization system obtained in the previous step, it is calendered into a 10.5mm thick film, and the forming temperature is controlled at 90℃. The formed blank is then left to stand at 25℃ for 13 hours to allow the paraffin oil, flame retardant filler, reinforcing filler, foaming agent, and vulcanizing agent to achieve a relatively balanced distribution within the rubber compound. During the curing process, the surface of the blank remains flat, without obvious oil separation, powdering, or pre-foaming.
[0089] S6. High-temperature plasticizing and foaming vulcanization: Based on the preform obtained in the previous step, it is placed in a flat vulcanizing equipment for high-temperature plasticizing and foaming vulcanization treatment. The treatment temperature is 172.5℃ and the treatment time is 15min. In the initial stage of heating, the rubber phase, paraffin oil and high part of halogen-free flame retardant are further integrated. In the middle stage, the foaming agent decomposes and releases gas and promotes the formation of cells in the rubber compound. In the later stage, the vulcanizing agent and crosslinking agent form a crosslinking network and fix the cell structure.
[0090] S7. Cooling, Shaping and Post-treatment: Based on the product that has been foamed and vulcanized in the previous step, the product is taken out of the flat vulcanizing equipment and allowed to cool naturally. After cooling to room temperature, it is cut, punched and trimmed. Then, it is subjected to a post-curing treatment at 75℃ for 2.5 hours.
[0091] Example 2:
[0092] A flame-retardant EPDM foamed rubber composition, comprising the following components by weight: 100 parts EPDM rubber, 35 parts ethylene-propylene copolymer, 60 parts paraffin oil, 180 parts aluminum hydroxide, 120 parts magnesium hydroxide, 60 parts intumescent flame retardant, 20 parts zinc borate, 25 parts carbon black, 20 parts silica, 8 parts zinc oxide, 3 parts stearic acid, 12 parts foaming agent, 8 parts foaming aid, 6 parts vulcanizing agent, 5 parts crosslinking aid, and 4 parts antioxidant.
[0093] Ethylene propylene diene monomer (EPDM) rubber, ethylene-propylene copolymer, and paraffin oil together form the foamed rubber matrix. Aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate together form the halogen-free flame retardant system. Foaming agent, foaming aid, vulcanizing agent, and crosslinking aid together form the foamed vulcanization system.
[0094] Ethylene propylene diene monomer (EPDM) rubber is an EPDM rubber with an ethylene content of 57.5% and a Mooney viscosity of 60, and the third monomer in the EPDM rubber is ethylene-ide norbornene.
[0095] The melt flow rate of the ethylene-propylene copolymer is 2.75 g / 10 min, and the Shore A hardness is 75 degrees.
[0096] The paraffin oil is a naphthenic paraffin oil with a kinematic viscosity of 120 mm² / s at 40°C and a flash point of 180°C.
[0097] Aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler, with aluminum hydroxide having an average particle size of 4.5 μm and magnesium hydroxide having an average particle size of 3.4 μm.
[0098] The intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components, and a charring agent, with a mass ratio of 32.5:12.5:12.5. The degree of polymerization of the ammonium polyphosphate is 500.
[0099] The average particle size of zinc borate is 3 μm, and the moisture content is 1.5%.
[0100] Carbon black and silica together constitute the reinforcing filler, with carbon black having an iodine absorption value of 50 mg / g and silica having a specific surface area of 170 m² / g.
[0101] The foaming agent is azodicarbonamide, with a decomposition temperature of 180℃; the foaming aid is a urea-based foaming aid.
[0102] The vulcanizing agent is dicumyl peroxide, and the crosslinking aid is triallyl isocyanurate.
[0103] A method for preparing a flame-retardant EPDM foamed rubber composition includes the following steps:
[0104] S1. Matrix Plasticizing Premix: Weigh out EPDM rubber, ethylene-propylene copolymer, and paraffin oil according to the formula mass parts. First, put the EPDM rubber into a mixer for initial plasticizing. After the rubber compound forms a continuous roll wrapping or continuous shearing state, add the ethylene-propylene copolymer and continue mixing to disperse the ethylene-propylene copolymer in the EPDM rubber to form a flexible rubber-plastic matrix. Then, add the paraffin oil in batches to allow the paraffin oil to gradually penetrate into the flexible rubber-plastic matrix. Control the mixing temperature at 87.5℃ and the mixing time at 7 minutes. When discharging, there should be no obvious free oil or unplasticized rubber lumps on the surface of the rubber compound.
[0105] S2. Halogen-free flame-retardant filler dispersion: Based on the flexible rubber-plastic matrix obtained in the previous step, aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate are sequentially added to a Banbury mixer for filler dispersion and mixing. Aluminum hydroxide and magnesium hydroxide are added first, allowing the two metal hydroxides to form a basic endothermic flame-retardant filler phase in the colloidal phase. Then, the intumescent flame retardant is added, dispersing it between the metal hydroxides. Finally, zinc borate is added, distributing it at the interface between the metal hydroxides and the intumescent flame retardant. The mixing temperature is controlled at 110℃, the mixing time at 10 minutes, and the discharge temperature at 135℃.
[0106] S3. Reinforcing and Stabilizing System Mixing: Based on the flame-retardant rubber compound obtained in the previous step, carbon black, silica, zinc oxide, stearic acid, and antioxidants are added and mixed further. This ensures that the carbon black and silica are dispersed within the cell skeleton formation area of the flame-retardant rubber compound, that zinc oxide and stearic acid are dispersed in the rubber phase to form a vulcanization-promoting auxiliary system, and that the antioxidants are dispersed in the continuous phase of the rubber compound. The mixing temperature in this stage is controlled at 110℃, and the mixing time is 5.5 minutes. After mixing, the rubber compound is thin-passed or re-mixed to control the compound thickness at 5.5 mm, and then cooled to room temperature.
[0107] S4. Low-temperature addition of foaming vulcanization system: Based on the rubber compound cooled in the previous step, transfer the rubber compound into the open mill, control the rubber compound temperature at 62.5℃, add the foaming agent, foaming aid, vulcanizing agent and crosslinking aid in sequence, and mix evenly for 5.5 minutes; during the mixing process, control the roller gap and rotor shear strength to ensure that the foaming agent and vulcanizing agent are evenly distributed without premature decomposition or premature crosslinking.
[0108] S5. Film Forming and Curing: Based on the rubber compound containing the foaming vulcanization system obtained in the previous step, it is calendered into a 10.5mm thick film, and the forming temperature is controlled at 90℃. The formed blank is then left to stand at 25℃ for 13 hours to allow the paraffin oil, flame retardant filler, reinforcing filler, foaming agent, and vulcanizing agent to achieve a relatively balanced distribution within the rubber compound. During the curing process, the surface of the blank remains flat, without obvious oil separation, powdering, or pre-foaming.
[0109] S6. High-temperature plasticizing and foaming vulcanization: Based on the preform obtained in the previous step, it is placed in a flat vulcanizing equipment for high-temperature plasticizing and foaming vulcanization treatment. The treatment temperature is 172.5℃ and the treatment time is 15min. In the initial stage of heating, the rubber phase, paraffin oil and high part of halogen-free flame retardant are further integrated. In the middle stage, the foaming agent decomposes and releases gas and promotes the formation of cells in the rubber compound. In the later stage, the vulcanizing agent and crosslinking agent form a crosslinking network and fix the cell structure.
[0110] S7. Cooling, Shaping and Post-treatment: Based on the product that has been foamed and vulcanized in the previous step, the product is taken out of the flat vulcanizing equipment and allowed to cool naturally. After cooling to room temperature, it is cut, punched and trimmed. Then, it is subjected to a post-curing treatment at 75℃ for 2.5 hours.
[0111] Example 3:
[0112] A flame-retardant EPDM foamed rubber composition, comprising the following components by weight: 100 parts EPDM rubber, 22.5 parts ethylene-propylene copolymer, 40 parts paraffin oil, 130 parts aluminum hydroxide, 80 parts magnesium hydroxide, 40 parts intumescent flame retardant, 12.5 parts zinc borate, 15 parts carbon black, 12.5 parts silica, 5.5 parts zinc oxide, 2 parts stearic acid, 8 parts foaming agent, 5 parts foaming aid, 4 parts vulcanizing agent, 3 parts crosslinking aid, and 2.5 parts antioxidant.
[0113] Ethylene propylene diene monomer (EPDM) rubber, ethylene-propylene copolymer, and paraffin oil together form the foamed rubber matrix. Aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate together form the halogen-free flame retardant system. Foaming agent, foaming aid, vulcanizing agent, and crosslinking aid together form the foamed vulcanization system.
[0114] Ethylene propylene diene monomer (EPDM) rubber is an EPDM rubber with an ethylene content of 57.5% and a Mooney viscosity of 60, and the third monomer in the EPDM rubber is ethylene-ide norbornene.
[0115] The melt flow rate of the ethylene-propylene copolymer is 2.75 g / 10 min, and the Shore A hardness is 75 degrees.
[0116] The paraffin oil is a naphthenic paraffin oil with a kinematic viscosity of 120 mm² / s at 40°C and a flash point of 180°C.
[0117] Aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler, with aluminum hydroxide having an average particle size of 4.5 μm and magnesium hydroxide having an average particle size of 3.4 μm.
[0118] The intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components, and a charring agent, with a mass ratio of 32.5:12.5:12.5. The degree of polymerization of the ammonium polyphosphate is 500.
[0119] The average particle size of zinc borate is 3 μm, and the moisture content is 1.5%.
[0120] Carbon black and silica together constitute the reinforcing filler, with carbon black having an iodine absorption value of 50 mg / g and silica having a specific surface area of 170 m² / g.
[0121] The foaming agent is azodicarbonamide, with a decomposition temperature of 180℃; the foaming aid is a urea-based foaming aid.
[0122] The vulcanizing agent is dicumyl peroxide, and the crosslinking aid is triallyl isocyanurate.
[0123] A method for preparing a flame-retardant EPDM foamed rubber composition includes the following steps:
[0124] S1. Matrix Plasticizing Premix: Weigh out EPDM rubber, ethylene-propylene copolymer, and paraffin oil according to the formula mass parts. First, put the EPDM rubber into a mixer for initial plasticizing. After the rubber compound forms a continuous roll wrapping or continuous shearing state, add the ethylene-propylene copolymer and continue mixing to disperse the ethylene-propylene copolymer in the EPDM rubber to form a flexible rubber-plastic matrix. Then, add the paraffin oil in batches to allow the paraffin oil to gradually penetrate into the flexible rubber-plastic matrix. Control the mixing temperature at 87.5℃ and the mixing time at 7 minutes. When discharging, there should be no obvious free oil or unplasticized rubber lumps on the surface of the rubber compound.
[0125] S2. Halogen-free flame-retardant filler dispersion: Based on the flexible rubber-plastic matrix obtained in the previous step, aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate are sequentially added to a Banbury mixer for filler dispersion and mixing. Aluminum hydroxide and magnesium hydroxide are added first, allowing the two metal hydroxides to form a basic endothermic flame-retardant filler phase in the colloidal phase. Then, the intumescent flame retardant is added, dispersing it between the metal hydroxides. Finally, zinc borate is added, distributing it at the interface between the metal hydroxides and the intumescent flame retardant. The mixing temperature is controlled at 110℃, the mixing time at 10 minutes, and the discharge temperature at 135℃.
[0126] S3. Reinforcing and Stabilizing System Mixing: Based on the flame-retardant rubber compound obtained in the previous step, carbon black, silica, zinc oxide, stearic acid, and antioxidants are added and mixed further. This ensures that the carbon black and silica are dispersed within the cell skeleton formation area of the flame-retardant rubber compound, that zinc oxide and stearic acid are dispersed in the rubber phase to form a vulcanization-promoting auxiliary system, and that the antioxidants are dispersed in the continuous phase of the rubber compound. The mixing temperature in this stage is controlled at 110℃, and the mixing time is 5.5 minutes. After mixing, the rubber compound is thin-passed or re-mixed to control the compound thickness at 5.5 mm, and then cooled to room temperature.
[0127] S4. Low-temperature addition of foaming vulcanization system: Based on the rubber compound cooled in the previous step, transfer the rubber compound into the open mill, control the rubber compound temperature at 62.5℃, add the foaming agent, foaming aid, vulcanizing agent and crosslinking aid in sequence, and mix evenly for 5.5 minutes; during the mixing process, control the roller gap and rotor shear strength to ensure that the foaming agent and vulcanizing agent are evenly distributed without premature decomposition or premature crosslinking.
[0128] S5. Film Forming and Curing: Based on the rubber compound containing the foaming vulcanization system obtained in the previous step, it is calendered into a 10.5mm thick film, and the forming temperature is controlled at 90℃. The formed blank is then left to stand at 25℃ for 13 hours to allow the paraffin oil, flame retardant filler, reinforcing filler, foaming agent, and vulcanizing agent to achieve a relatively balanced distribution within the rubber compound. During the curing process, the surface of the blank remains flat, without obvious oil separation, powdering, or pre-foaming.
[0129] S6. High-temperature plasticizing and foaming vulcanization: Based on the preform obtained in the previous step, it is placed in a flat vulcanizing equipment for high-temperature plasticizing and foaming vulcanization treatment. The treatment temperature is 172.5℃ and the treatment time is 15min. In the initial stage of heating, the rubber phase, paraffin oil and high part of halogen-free flame retardant are further integrated. In the middle stage, the foaming agent decomposes and releases gas and promotes the formation of cells in the rubber compound. In the later stage, the vulcanizing agent and crosslinking agent form a crosslinking network and fix the cell structure.
[0130] S7. Cooling, Shaping and Post-treatment: Based on the product that has been foamed and vulcanized in the previous step, the product is taken out of the flat vulcanizing equipment and allowed to cool naturally. After cooling to room temperature, it is cut, punched and trimmed. Then, it is subjected to a post-curing treatment at 75℃ for 2.5 hours.
[0131] Comparative Example 1:
[0132] Without ethylene-propylene copolymer, used for comparison of low hardness and cell stability: 100 parts EPDM rubber, 40 parts paraffin oil, 130 parts aluminum hydroxide, 80 parts magnesium hydroxide, 40 parts intumescent flame retardant, 12.5 parts zinc borate, 15 parts carbon black, 12.5 parts silica, 5.5 parts zinc oxide, 2 parts stearic acid, 8 parts foaming agent, 5 parts foaming aid, 4 parts vulcanizing agent, 3 parts crosslinking aid, and 2.5 parts antioxidant.
[0133] Excluding the preparation steps related to the ethylene-propylene copolymer, the rest are the same as in Examples 1-3.
[0134] Comparative Example 2:
[0135] Without the addition of intumescent flame retardant and zinc borate, and with an equal amount of metal hydroxide added, the synergistic flame retardant effect was compared: 100 parts EPDM rubber, 22.5 parts ethylene-propylene copolymer, 40 parts paraffin oil, 170 parts aluminum hydroxide, 92.5 parts magnesium hydroxide, 15 parts carbon black, 12.5 parts silica, 5.5 parts zinc oxide, 2 parts stearic acid, 8 parts foaming agent, 5 parts foaming aid, 4 parts vulcanizing agent, 3 parts crosslinking aid, and 2.5 parts antioxidant.
[0136] Excluding the preparation steps related to the intumescent flame retardant and zinc borate, the rest are the same as in Examples 1-3.
[0137] The compositions prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the tests shown in Table 1 below to verify the actual effect of the compositions.
[0138] Table 1
[0139] 1 Appearance and cell structure Take samples after foaming and vulcanization and observe the surface and cross-section conditions; if necessary, use a magnifying glass or microscope to observe the continuity of the foam cells. The surface showed no obvious scorching, cracks, delamination, collapse, or large-area pores; the cross-section showed uniform pore distribution and no obvious filler agglomeration points. 2 Shore A hardness Test the surface hardness of the finished product according to GB / T 531.1 or an equivalent method; for products with low hardness, a sufficiently thick stack of sheets should be used for testing. The hardness meets the target design value; when used for low-hardness foam, the target hardness can be set to 10-25 degrees, and the fluctuation of a single batch of samples should not exceed ±5 degrees. 3 Apparent density The apparent density of foamed products shall be tested according to GB / T 6343 or an equivalent method. The apparent density meets the target design value; the density fluctuation of the same batch of samples is no more than ±10%, and there are no obvious local high-density hard lumps. 4 Foaming ratio The foaming ratio can be calculated based on the density of the unfoamed rubber compound and the apparent density of the foamed product, or according to the method confirmed by the company. The expansion ratio meets the target design value; the example should demonstrate a high expansion ratio, and the comparative example is used to compare the situation of decreased expansion ratio or cell instability. 5 Tensile strength and elongation at break Tensile strength and elongation at break shall be tested according to GB / T 528 or equivalent methods. The results should meet the design requirements of the corresponding sealing, heat insulation gaskets or flame-retardant foam; brittle fracture should not occur before heat aging. 6 Compression permanent deformation Test according to GB / T 7759.1 or equivalent method. Test conditions can be selected as 70℃×22h or determined according to customer's working conditions. The permanent compression deformation is no more than 30%, or meets the customer's compression recovery requirements for seals and gaskets in new energy vehicles. 7 Dimensional shrinkage The sample is heat-treated at 70℃ for 24 hours or under specified conditions, and the changes in length, width or thickness before and after treatment are measured. The shrinkage rate in the length and width directions shall not exceed 5%; irreversible collapse shall not occur in the thickness direction. 8 Flame retardant properties Test according to the UL 94 vertical burning method; the sample thickness is prepared according to the actual product thickness or the standard specified thickness. It meets the UL 94 V-0 rating; it is self-extinguishing after being removed from the flame and does not produce burning droplets that could ignite absorbent cotton. 9 Oxygen Index The limiting oxygen index shall be tested according to GB / T 2406.2 or an equivalent method. The oxygen index should be no less than 28%, and can be increased to no less than 30% when used in products with high flame retardancy rating. 10 Low halogen content Test the halogen content (chlorine, bromine, etc.) according to IEC 62321, EN 14582 or customer-approved methods. The individual and total amounts of chlorine and bromine meet the customer's low-halogen requirements; when a halogen-free declaration is required, it can be determined according to the halogen-free limit specified by the customer. 11 Hot air aging Perform hot air aging according to GB / T 3512 or equivalent methods. Test conditions can be selected as 100℃×72h or determined according to the operating conditions. After aging, there is no obvious powdering, cracking, or adhesion; the hardness change is no more than ±5 degrees, and the tensile property retention rate is no less than 70%. 12 Water absorption or water resistance Test the changes in quality and appearance after immersion in water according to GB / T 1690, GB / T 1034 or customer-approved methods. After immersion in water, there is no delamination, cracking, or significant expansion; the rate of change in mass is no more than 5%, or it meets the design requirements for sealed and waterproof products. 13 Combustion smoke and char layer condition After the flame retardant test, the combustion residue, char layer integrity, and smoke state are observed as evaluations of the flame retardant synergistic effect. A continuous char layer forms on the combustion surface, with minimal cracking and detachment of the char layer; the smoke and residue meet the customer's safety evaluation requirements.
[0140] The test results are summarized as follows:
[0141] As can be seen from Examples 1 to 3, this invention, based on EPDM rubber, utilizes the synergistic effects of ethylene-propylene copolymer, paraffin oil, aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, zinc borate, and a foaming vulcanization system to enable the composition to form a stable flame-retardant foamed rubber system at different formulation endpoints and intermediate dosages. Example 1 uses a lower filler content and a lower foaming vulcanization system dosage, mainly to verify that the composition can still form a foamable and vulcanizable foam structure under conditions of low flame retardant and low additive addition. Example 2 uses a higher filler content and a higher foaming vulcanization system dosage, mainly to verify that the composition can still maintain processability, cell stability, and dimensional stability after the addition of a large amount of halogen-free flame retardant. Example 3 uses an intermediate dosage, mainly to verify that the composition has a good overall balance between flame retardant performance, hardness adjustment, foaming ratio, and density stability. The above three embodiments collectively illustrate that the formulation of the present invention does not rely on a single component to achieve flame retardancy or foaming. Instead, it achieves this through the matching of the flexible rubber and plastic matrix, the halogen-free composite flame retardant system, the reinforcing and stabilizing system, and the foaming and vulcanization system, enabling the material to adapt to the different usage requirements of sealing, waterproofing, and flame retardant components for new energy vehicles and heat insulation and flame retardant protective components for photovoltaic power generation and energy storage cabinets.
[0142] Compared to Example 3, Comparative Example 1 did not include ethylene-propylene copolymer. Although EPDM rubber could still be used as the main rubber for foaming and vulcanization, the presence of a high proportion of halogen-free flame retardant resulted in insufficient flexibility and flame-retardant filler inclusion in the rubber compound. This easily led to increased filler dispersion resistance during mixing, decreased cell wall continuity after foaming, increased finished product hardness, and a narrower low hardness adjustment range. Therefore, Comparative Example 1 mainly serves to illustrate that ethylene-propylene copolymer is not simply a filler or substitute resin, but rather plays a role in reducing the hardening tendency of the rubber compound, improving filler dispersion, maintaining the low-hardness foam structure, and improving cell stability in a high-flame-retardant filled system. This ensures that the composition achieves flame-retardant properties while still possessing the softness required for sealing, waterproofing, and cushioning.
[0143] Compared to Example 3, Comparative Example 2 did not include intumescent flame retardant and zinc borate. Instead, it maintained a high content of halogen-free flame-retardant filler by increasing aluminum hydroxide and magnesium hydroxide. This comparative example demonstrates that when flame retardancy is achieved solely through the endothermic dehydration of metal hydroxides, it is difficult to form a stable, dense, and continuous intumescent char layer on the material surface. The material's ability to block heat and oxygen during combustion is insufficient, resulting in relatively limited self-extinguishing performance and char layer integrity. Furthermore, simply increasing the amount of metal hydroxide added increases the mixing load and system viscosity of the rubber compound, easily affecting the foaming ratio and cell uniformity. Therefore, Comparative Example 2 primarily demonstrates the synergistic flame-retardant effect between the intumescent flame retardant and zinc borate, and aluminum hydroxide and magnesium hydroxide, achieving a balance between flame retardant rating, smoke suppression and char stabilization effects, and foam structure stability under high halogen-free filling conditions.
[0144] Evaluation based on the test items of the comprehensive embodiments and comparative examples reveals that the technical effects of the composition of the present invention are mainly reflected in the following aspects: First, the flexible rubber-plastic matrix formed by EPDM rubber, ethylene-propylene copolymer, and paraffin oil allows the material to achieve low hardness and good compression resilience even under high flame retardant filling conditions; second, the composite halogen-free flame retardant system composed of aluminum hydroxide, magnesium hydroxide, intumescent flame retardant, and zinc borate enables the material to possess low halogen content, self-extinguishing properties, and good surface heat insulation and flame retardant capabilities; third, the combination of carbon black, silica, and the foaming and vulcanization system allows the foam to form a relatively stable cell skeleton after high-temperature plasticization, foaming, and vulcanization, reducing dimensional shrinkage and density fluctuations. Therefore, this application solves the problems of increased hardness, decreased foaming ratio, unstable shrinkage, and dispersed product density that easily occur in existing flame-retardant EPDM foamed rubber after increasing the flame retardant content, making it suitable for preparing sealing, waterproofing, heat insulation, and flame-retardant protective materials for new energy vehicles and photovoltaic energy storage cabinets.
[0145] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A flame-retardant EPDM foamed rubber composition, characterized in that, By mass parts, it includes the following components: 100 parts EPDM rubber, 10-35 parts ethylene-propylene copolymer, 20-60 parts paraffin oil, 80-180 parts aluminum hydroxide, 40-120 parts magnesium hydroxide, 20-60 parts intumescent flame retardant, 5-20 parts zinc borate, 5-25 parts carbon black, 5-20 parts silica, 3-8 parts zinc oxide, 1-3 parts stearic acid, 4-12 parts foaming agent, 2-8 parts foaming aid, 2-6 parts vulcanizing agent, 1-5 parts crosslinking aid, and 1-4 parts antioxidant. The EPDM / POE composite rubber matrix is formed by combining the EPDM and ethylene-propylene copolymer in the specified mass parts. The ethylene-propylene copolymer is dispersed in the continuous phase of the EPDM rubber to form a biphase blend structure with a rubber elastic phase and a flexible polyolefin phase. The EPDM / POE composite rubber matrix and paraffin oil together constitute the foamed rubber matrix. The aluminum hydroxide, magnesium hydroxide, intumescent flame retardant and zinc borate together form a halogen-free flame retardant system. The foaming agent, foaming aid, vulcanizing agent and crosslinking aid together form a foaming vulcanization system. The EPDM / POE composite rubber matrix is used to maintain the processing fluidity and cell support capacity of the rubber compound under the condition of adding high content of halogen-free flame retardant filler, so that the composition forms a stable cell structure after foaming and vulcanization. This flame-retardant EPDM foamed rubber composition is used as a foamed rubber material for sealing, waterproofing, and flame-retardant components of new energy vehicles or for heat-insulating and flame-retardant protective components of photovoltaic power generation energy storage cabinets.
2. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The EPDM rubber is an EPDM rubber with an ethylene content of 45%-70% and a Mooney viscosity of 40-80, and the third monomer in the EPDM rubber is ethylene-ide norbornene.
3. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The melt flow rate of the ethylene-propylene copolymer is 0.5-5 g / 10 min, and the Shore A hardness is not higher than 75 degrees. The ethylene-propylene copolymer and EPDM rubber are melt-blended to form an EPDM / POE composite rubber matrix, wherein the ethylene-propylene copolymer is distributed in the interstitial region of the EPDM rubber molecular chains to improve the flexibility and filler capacity of the composite rubber matrix.
4. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The aluminum hydroxide and magnesium hydroxide together constitute the main flame-retardant filler, wherein the average particle size of aluminum hydroxide is 1-8 μm and the average particle size of magnesium hydroxide is 0.8-6 μm.
5. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The intumescent flame retardant is composed of ammonium polyphosphate, melamine-based components and a charring agent, with a mass ratio of 20-45:5-20:5-20, and the degree of polymerization of the ammonium polyphosphate is not less than 500. By limiting the composition of the acid source, gas source and carbon source of the intumescent flame retardant, an intumescent carbon layer is formed on the surface of the foam when the material is exposed to fire. This intumescent carbon layer covers the surface of the EPDM foamed rubber and prevents heat and oxygen from continuing to enter the internal cell structure.
6. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The zinc borate has an average particle size of 1-5 μm and a moisture content of no more than 1.5%. The zinc borate is dispersed between the metal hydroxide and the intumescent flame retardant to form a boron-containing glass-like protective layer on the burning surface and to improve the density and crack resistance of the intumescent char layer.
7. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The carbon black and silica together constitute the reinforcing filler, wherein the carbon black has an iodine absorption value of 20-80 mg / g and the silica has a specific surface area of 120-220 m² / g.
8. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The foaming agent is azodicarbonamide or modified azodicarbonamide, with a decomposition temperature of 150-210℃; The foaming agent is zinc oxide, urea-based foaming agents, or a combination thereof.
9. The flame-retardant EPDM foamed rubber composition according to claim 1, characterized in that, The vulcanizing agent is a peroxide vulcanizing agent, and the crosslinking aid is triallyl isocyanurate or trimethylolpropane trimethacrylate; By forming a heat-resistant crosslinking network through peroxide vulcanizing agent and crosslinking aid, EPDM rubber, ethylene-propylene copolymer and flame-retardant filler are fixed into a stable cell skeleton after high-temperature plasticization.
10. A method for preparing a flame-retardant EPDM foamed rubber composition, comprising the flame-retardant EPDM foamed rubber composition according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Matrix plasticizing premix: EPDM rubber, ethylene-propylene copolymer and paraffin oil are mixed to form a flexible rubber-plastic matrix; S2, Halogen-free flame retardant filler dispersion: Add aluminum hydroxide, magnesium hydroxide, intumescent flame retardant and zinc borate to form a composite flame retardant system; S3, Reinforcing and Stabilizing System Mixing: Add carbon black, silica, zinc oxide, stearic acid and antioxidants to improve the stability of the cell skeleton; S4. Low-temperature addition to the foaming and vulcanization system: Add the foaming agent, foaming aid, vulcanizing agent, and crosslinking aid at a temperature below the decomposition temperature of the foaming agent; S5. Film forming and curing: The rubber material is calendered or extruded into a blank and then cured to ensure a balanced distribution of components. S6. High-temperature plasticizing and foaming vulcanization: The preform is subjected to high-temperature plasticizing, foaming and vulcanization to expand the cell structure and cross-link and solidify it. S7. Cooling, shaping and post-treatment: Cooling, cutting or post-curing the foamed vulcanized products to obtain flame-retardant foamed rubber products.
